2002
DOI: 10.1088/0957-4484/13/5/327
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for preparing ultra-fine alumina-borate oxide fibres via an electrospinning technique

Abstract: Alumina-borate/PVA composite fibres were prepared using sol–gel processing and an electrospinning technique. After calcination of the thin fibres, ultra-fine fibres of alumina-borate oxide with a diameter of about 550 nm could be prepared. The fibres were characterized by SEM, XRD and FT-IR. The results showed that the crystalline phase and morphology of alumina-borate fibres were largely influenced by the calcination temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
99
3
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(106 citation statements)
references
References 20 publications
2
99
3
2
Order By: Relevance
“…3 The feasibility to construct long and continuous polymeric, [4][5][6] ceramic, 7 and composite 8 nanofibers as well as nanotubes 9 with diameters less than 100 nm has been demonstrated using electrospinning. Typical applications include bioscaffolding, 10 wound dressing, 11 and filtrations 12 to name a few.…”
mentioning
confidence: 99%
“…3 The feasibility to construct long and continuous polymeric, [4][5][6] ceramic, 7 and composite 8 nanofibers as well as nanotubes 9 with diameters less than 100 nm has been demonstrated using electrospinning. Typical applications include bioscaffolding, 10 wound dressing, 11 and filtrations 12 to name a few.…”
mentioning
confidence: 99%
“…The fabrication of such nanostructured materials in well-defined and monodispersed forms with controlled length scales has been a major challenge in materials science and engineering. Recently, electrostatic spinning [3,4] has been shown to be an efficient and facile method to prepare fine fibers and, following the use of pyrolytic techniques, has been used to make carbon, [5] silica, [6] alumina borate, [7] titania, [8,9] alumina, [10] niobium oxide, [11] and some composite fibers such as nickel ferrite. [12] However, we are unaware of any research on the fabrication of non-oxide ceramics via electrostatic spinning of polymeric precursors.…”
Section: Methodsmentioning
confidence: 99%
“…Dai et al have reported the synthesis of alumina-borate composite fibers by electrospinning, starting from a mixture of aluminum acetate stabilized with boric acid in 10% aqueous solution of PVA, followed by calcination. 9) They obtained fibers thicker than 0.5 μm upon firing the composite up to 1400°C.…”
Section: )3)mentioning
confidence: 99%